Luke : An Introduction and Commentary - Perrin, Nicholas (Downers Grove.: : IVP Academic, 2022)
In this insightful and accessible biblical commentary, Nicholas Perrin explores the many unique pictures of Jesus found in the Gospel of Luke from being a child in his Father s house to associating with the poor and disreputable, in communion with the Holy Spirit, and, above all, setting out resolutely for Jerusalem to fulfil God s plan for the world. With particular attention to the redemptive-historical storyline and its scriptural roots, Perrin examines how Luke s Gospel is embedded in human history. He also show how it follows a cyclical narrative structure, with each recapitulation expanding the horizons of what has gone before. Part of the Tyndale New Testament commentary series, Luke: An Introduction and Commentary examines the text section-by-section exploring the context in which it was written, providing astute commentary on Luke s Gospel, and then unpacking the theology. It will leave you with a thorough understanding of the content and structure Gospel of Luke, as well as what it means and its continued relevance for Christians today. The Tyndale New Testament Commentaries are ideal Bible commentaries for students and teachers of theology, as well as being usable for preachers and individual Christians looking to delve deeper into the riches of Scripture and discover its meaning for today. Perceptive, cogent and thorough, Nicholas Perrin s commentary on Luke will give you a renewed appreciation for Luke s Gospel and a greater understanding of why it is such a vital part of Scripture.